Kesesuaian Penggunaan Alat Tangkap Purse Seine dengan Kebijakan Penangkapan Ikan Terukur di Wilayah Pengelolaan Perikanan (WPP) 572 - Nurlaela, Eli; Nasution, Aulia Rahman; Saputra, Aman; Purwanto, Yuli; Choerudin, Hery; Perangin-angin, Robet; Tofani, Anam (Politeknik Kelautan dan Perikanan Bitung, 2024)
This study evaluates the compatibility of purse seine fishing gear with the Measured Fishing Policy (PIT) implemented in Fisheries Management Area (WPP) 572, particularly in the waters of Sibolga, a central hub of fishing activities at the Sibolga National Fisheries Port (PPN Sibolga). The PIT policy aims to sustainably manage fishery resources through catch quotas and output control. The focus of this study is on the alignment of fish caught using purse seine with the Measured Fishing Policy (PIT). The catch data from KM. Muara Agung were analyzed descriptively, covering the composition of catches from trip I, II, and III. In trip I, total catches reached 3,193 kg, dominated by tongkol (49%). In trip II, catches increased to 7,749 kg, with tongkol accounting for 53%. In trip III, total catches were 10,942 kg, with tongkol as the dominant species (51.63%). Although purse seine effectively captures target species in line with PIT policy, the identified bycatch requires better management to ensure ecosystem sustainability. This study offers recommendations for more data-driven and holistic management strategies, with an emphasis on bycatch management, and identifies challenges in the implementation of PIT policy in WPP 572 and PPN Sibolga.